Morpho-biochemical, antioxidant and pigmentation in different genotypes of pummelo fruits (Citrus maxima) in Meghalaya - RYMBAI, HEIPLANMI; JHA, A K; TALANG, HAMMYLLIENDE; DEVI, M B; RAVITEJA, P; VERMA, V K; RYMBAI, D; MAWLEIN, J; HAZARIKA, S (The Indian Journal of Agricultural Sciences, 2025)
Pummelo [Citrus maxima (Burm.) Merr.] is a potential commercial citrus due to its wide adaptability, economic, and health benefits. In spite of the vast genetic resources of citrus, the lack of systematic characterization has primarily caused significant gaps in understanding the valuable traits of pummelo, resulting in their sparing utilisation. The present study was carried out during 2021–2023 at ICAR Research Complex NEH Region, Umiam, Meghalaya to evaluate 14 genotypes of pummelo to identify the ideal genotypes and popularise the crop. Ten fully mature and healthy fruits from each genotype were collected randomly in different directions of the canopy with three replications. The results showed significant variations in fruit morphology, biochemical, antioxidant and pigmentation among different genotypes of pummelo. The highest fruit weight was found in RCCG-07 (900.3±57.5 g), pulp in RCCG-05 (74.0±2.2%), and juice content in RCCG-14 (49.5±2.8%). The maximum TSS (11.1±0.4%) and total carbohydrates (44.6±2.7 mg glucose/ml) were recorded in RCCG-07; vitamin C (97.6±2.9 mg/100 ml) and carotenoids (140.1±7.1 µg/100 ml) in RCGH-06. Furthermore, total phenolic content was obtained the maximum in RCCG-09, total flavonoid in RCCG-05, FRAP in RCCG-08, and pulp a* value in RCCG-06. The correlation indicated that ascorbic acid, carotenoids, and flavonoids contributed significantly to the antioxidant properties of this fruit. It was also found that the white-fleshed genotypes had higher fruit weight, pulp, and juice content, with fewer seeds. The quality attributes, including biochemical, antioxidant and pigmentation, were higher in red-fleshed genotypes; however, such traits may be associated with a higher seed number. Therefore, RCCG-05 (white-fleshed) and red-fleshed genotypes (RCCG-06 and RCCG-07) with higher fruit weight, pulp, and biochemical, antioxidant and pigmentation quality, can be ideal genotypes suitable for incorporation in breeding programmes, popularisation, and processing industries.